2011
DOI: 10.1002/mabi.201000437
|View full text |Cite
|
Sign up to set email alerts
|

Image Printing on the Surface of Anti‐Biofouling Zwitterionic Polymer Brushes by Ion Beam Irradiation

Abstract: A CMB monomer was polymerized on a glass plate with a surface-confined ATRP initiator containing a 2-bromoisobutyryl group. The glass plate modified with a PCMB brush was highly hydrophilic and showed a strong resistance against non-specific adsorption of proteins and cell adhesion. Upon ion beam irradiation, furthermore, the PCMB brush was ablated and a hollow space with a designed shape could be made to which HEK293 cells (from human embryonic kidney) and Hep G2 (from human hepatoma) cells non-specifically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Zwitterionic polymers, which have both anion and cation in a single molecule, are known as excellent bio-functional materials that prevent both cell adhesion and protein adsorption [17,18] , and are also useful for bio-patterning [19,20] . In this work, zwitterionic polymers were prepared using 1-carboxy-N,Ndimethyl-N-(2'-methacryloyloxyethyl)methanaminium inner salt also known as carboxymethyl betaine (CMB) was kindly donated from Osaka Organic Chemical Industry, Kashiwara, Japan, and n-butylmethacrylate (BMA) obtained from Wako, Osaka, Japan, at the rate of (CMB/BMA = 29/71; MW = 193 kDa and MW/Mn =1.92; 1 wt% ethanol solution), and utilized as a surface patterning material.…”
Section: Preparation Of Surface Patterned Discs With Non-cell-adherenmentioning
confidence: 99%
“…Zwitterionic polymers, which have both anion and cation in a single molecule, are known as excellent bio-functional materials that prevent both cell adhesion and protein adsorption [17,18] , and are also useful for bio-patterning [19,20] . In this work, zwitterionic polymers were prepared using 1-carboxy-N,Ndimethyl-N-(2'-methacryloyloxyethyl)methanaminium inner salt also known as carboxymethyl betaine (CMB) was kindly donated from Osaka Organic Chemical Industry, Kashiwara, Japan, and n-butylmethacrylate (BMA) obtained from Wako, Osaka, Japan, at the rate of (CMB/BMA = 29/71; MW = 193 kDa and MW/Mn =1.92; 1 wt% ethanol solution), and utilized as a surface patterning material.…”
Section: Preparation Of Surface Patterned Discs With Non-cell-adherenmentioning
confidence: 99%
“…1–6 Cell micropatterning can be achieved with fouling resistant materials that enable selective cell adhesion while limiting the non-specific adsorption of biomolecules. 715 Currently, poly(ethylene glycol) (PEG) is the most widely-used antifouling polymer for grafting and lithographical patterning. 1014 However, the polyether structure and terminal hydroxyl groups of PEG leads to oxidative degradation in the presence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Protein molecules are adsorbed to the bare glass by hydrogen bonding between the protein molecules and the OH groups of the glass surface (Si‐OH). It has been reported that negatively charged BSA non‐specifically adsorbs to both poly(methacrylic acid) (PMA, negatively charged) and poly( N , N ‐dimethylaminoethyl methacrylate) (PDMAEMA, positively charged) brushes irrespective of their charge, but that BSA does not significantly adsorb to either the amphoteric polymer brush (poly(MA‐ r ‐DMAEMA), MA:DMAEMA = 1:1) or the zwitterionic polymer brushes, poly(sulfopropylbetaine) (PSPB) and PCMB . This indicates the importance of zwitterionic side chains in the suppression of non‐specific protein adsorption: protein that attaches to the S‐PCMB x layer can later be removed while still retaining its native structure …”
Section: Discussionmentioning
confidence: 99%
“…A similar tendency was observed for zwitterionic copolymer films, zwitterionic and amphoteric (charge‐neutralized) polymer brushes, and self‐assembled monolayers using the sum frequency generation method. Taking into account the resistance of zwitterionic and amphoteric copolymer films and polymer brushes to the non‐specific adsorption of proteins and cell adhesion, it is possible that one of the most important factors responsible for the biocompatibility of these materials is that they do not significantly alter the local structure of water. Furthermore, the degree of copolymer coverage, which is a function of both the average length of zwitterionic polymer loops and the average number of fixation points along the copolymer chain, is an important contributor to the anti‐biofouling properties of the modified surfaces.…”
Section: Discussionmentioning
confidence: 99%